Power, perspective, and privilege: The challenge of translating stakeholder theory from business management to environmental and natural resource management. (1st October 2020) - Colvin, R.M.; Witt, G. Bradd; Lacey, Justine
Abstract: Stakeholder analysis and engagement is a central tenet for understanding and solving sustainability challenges, and is applied widely in environmental and natural resource management (ENRM). The practice in ENRM follows translation of stakeholder theory from its origins in business management to the sustainability sector. In this analytical essay we explore key concepts in ENRM research and practice to examine complexities that have accompanied this translation to ENRM. In particular, we consider the centrality of stakeholders' landscape perspectives in defining their stake in ENRM issues, and through this lens examine the limitations that are inherent in the classic 'hub-and-spoke' model of stakeholder analysis that is the theoretical underpinning for ENRM stakeholder analysis and engagement practice. We argue that unlike the traditional business context where both power and perspective are centred on the business entity that then defines other stakeholders in reference to itself, in ENRM, stakeholder relations are centred on an ENRM issue, typically a landscape or the implications of policy change on a landscape. As a consequence, decision-making power is decentred onto one of several stakeholders; often a government or other high power entity, implicitly conferring privilege to those powerful stakeholders' landscape perspectives over those held by low power stakeholders. We conclude with priorities for foregrounding power and explicating landscape perspectives to identify privilege in ENRM. We direct these insights especially to those ENRM actors who have the dual roles of adjudicator and privileged stakeholder such that they do not inadvertently perpetuate power imbalances through the privilege of aligning their decision-making power with their landscape perspectives. Highlights: Stakeholder theory was developed in business management, in the context of the firm. It has since been translated to environmental and natural resource management. This translation creates privileges regarding power and landscape perspectives. Some actors can be both stakeholder and adjudicator – a privileged position. We propose pathways to recognise and mediate these privileges in ENRM.